Viruses and the aetiology of diabetes: a study in identical twins. Issue 5991 (1st November 1975) - Nelson, P G; Pyke, D A; Gamble, D R
Abstract : Sera were collected from 49 pairs of identical twins, 27 of whom were discordant (only one twin affected) and 22 concordant (both diabetic) for insulin-dependent diabetes. All were tested for antibodies to mumps, cytomegalovirus, rubella, Coxsackie virus types B1-5, and Mycoplasma pneumoniae. The diabetic co-twins had no more antibodies to any of the viruses than the non-diabetic co-twins of the discordant pairs. Antibodies to Coxsackie B2, rubella virus, and M pneumoniae were found more often in the discordant than in the concordant twins. In 30 of the 71 diabetic twins symptoms began when they were aged 4-6 years or 10-15 years. More concordant than discordant twins were diagnosed during the months January to March. Hence there was no direct evidence of a virus aetiology of juvenile onset diabetes in these twins, and the difference in antibody titres between the concordant and discordant twins was in keeping with a genetic difference between them. The age and time of onset suggested that environmental factors may be important in causing diabetes in the twins.